Alternative sanctions and measures in the criminal justice system of Slovenia - Šelih Alenka (Temida)
The paper presents the ways of introducing both material and procedural alternative measures into the criminal justice system of Slovenia from the beginning of 1990s, particularly into the Criminal Code and the Code of Criminal Procedure in 1995 (with the further amendments). That relates to both adult and juvenile offenders. Regarding implementation, the author emphasizes characteristics of the implementation of both groups of institutions; pays attention to the fact that procedural institutions are more important for prosecution of minor criminal offences; points out the importance of the personal factor that contributes to the implementation of new provisions; and gives an overview of the first experiment in the Slovenian judiciary related to that. The author gives an analysis of problems dealt with in the Slovenian doctrine and judicial practice in connection with alternative ways of proceeding; she points out, in particular, the imperfections of legal solutions; the unclear competences in implementation of alternative sanctions and problems resulting from such a situation.